Auto Lavaggio: Innovation and Digitalization in the Car Wash Industry - Adha, Fajar; Muhammad Fitri Saputra; Anisa, Nor (INSTALL: Information System and Technology Journal, 2024)
The car wash industry continues to grow with the adoption of digital technology to improve operational efficiency and service quality. This study aims to develop a digital application that supports the auto lavaggio business with key features such as online reservations, service process automation, and data-based performance reporting. This application was developed using the Django framework for the backend and Flutter for the user interface, with testing carried out using the black-box testing method. The results of the study show that this application has succeeded in increasing service efficiency by up to 40%, reducing customer waiting time, and providing ease of transactions through the integration of a digital payment system. In addition, the reporting dashboard feature provided allows business owners to monitor business performance in real-time, increasing transparency and making more informed decisions. Although this application has succeeded in providing significant benefits, challenges such as payment API integration and user adaptation to new technologies remain. The solutions implemented include system optimization and the addition of tutorial features for new users. Overall, this application provides an innovative solution in improving the services and operations of the auto lavaggio business, while opening up opportunities for further development, such as the use of artificial intelligence (AI) and the expansion of environmentally friendly services.